2015
DOI: 10.4172/2167-1044.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Disease Related Factors Affecting Non-adherence among Patients on Long Term Therapy of Antidepressants

Abstract: Introduction: Depression is a term used to describe a health problem in which mood pattern will be affected. Clinical depression is more severe and the symptoms can continue for weeks, months, and even years in some cases if it is not treated and it does interfere with our ability to function and it also can leads to suicide at its worst. Although clinical guidelines recommend antidepressants be continued for at least 6 months after symptom remission, approximately one third of patients discontinue antidepress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…A ten-year cumulative evidence reported that approximately fifty percent of depression patients discontinue their medications [ 28 ]. Sriharsha (2015) has reported that various factors such as duration of therapy and disease were found to influence adherence [ 29 ]. Our study has also found that long-standing depression and comorbid psychiatric features increased the chance of nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…A ten-year cumulative evidence reported that approximately fifty percent of depression patients discontinue their medications [ 28 ]. Sriharsha (2015) has reported that various factors such as duration of therapy and disease were found to influence adherence [ 29 ]. Our study has also found that long-standing depression and comorbid psychiatric features increased the chance of nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la depresión no se encontraron estudios en Colombia que midieran la adherencia a los antidepresivos; sin embargo, en India, un importante estudio transversal de 103 pacientes psiquiátricos con diagnóstico de depresión unipolar reportó un 44% con deficiente adherencia farmacológica, agregado a un 26% con una "justa" adherencia, la cual agrupan como no-adherente. No fue significativo el tipo de medicamento, pero el estudio resalta el valor estadísticamente significativo de la polifarmacia oral (p< 0.043) (16). La polifarmacia se define simplemente como el uso de múltiples medicamentos por un paciente, aunque el número mínimo preciso de los medicamentos utilizados para definir "polifarmacia" es variable.…”
Section: Discussionunclassified
“…15 Despite the existence of effective treatments, successful treatment, and response remain sub-optimal. 16 Over 20 years, adherence to medications in MDD has been an intractable clinical challenge. 17 Despite the high rate of medication nonadherence, there is a variation of adherence rate related to various methods used to measure medication adherence including self-reported, pill counts, pharmaceutical claims, biomarkers, physiological measures, and electronic medication monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…16 Over 20 years, adherence to medications in MDD has been an intractable clinical challenge. 17 Despite the high rate of medication nonadherence, there is a variation of adherence rate related to various methods used to measure medication adherence including self-reported, pill counts, pharmaceutical claims, biomarkers, physiological measures, and electronic medication monitoring. 4,18 Moreover, adherence to medication has been influenced by complex and multidimensional factors as barriers to reach successful treatment that includes patientrelated, therapy-related, healthcare system, condition-related, and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation